Simplifique ou resolva essa equação fatorial
![\frac{(n - 1)}{(n + 1) - n} = \frac{1}{81} \frac{(n - 1)}{(n + 1) - n} = \frac{1}{81}](https://tex.z-dn.net/?f=+%5Cfrac%7B%28n+-+1%29%7D%7B%28n+%2B+1%29+-+n%7D+%3D++%5Cfrac%7B1%7D%7B81%7D++)
Soluções para a tarefa
Respondido por
1
Resposta:
Explicação passo-a-passo:
obs o valor n= -9 não nos interessa
Perguntas interessantes
Matemática,
10 meses atrás
Matemática,
10 meses atrás
Química,
10 meses atrás
Administração,
1 ano atrás
Física,
1 ano atrás
Matemática,
1 ano atrás